2016
DOI: 10.1016/j.lfs.2016.10.025
|View full text |Cite
|
Sign up to set email alerts
|

Bladder overactivity involves overexpression of MicroRNA 132 and nerve growth factor

Abstract: Aim Here, we assessed the expression of non-protein coding microRNAs (miRs), nerve growth factor and inflammatory molecules in the rat model of acetic acid induced bladder overactivity. Main Methods Under isoflurane anesthesia, adult female Sprague-Dawley rats were instilled for 30 min with either saline or NGF antisense oligonucleotides complexed with liposomes. 24h later, treated rats were exposed to either intravesical infusion of saline or saline containing 0.25% acetic acid at the rate of 0.04ml/min for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 35 publications
0
14
0
1
Order By: Relevance
“…In investigations of effective miRNAs in smooth muscle, Chiba et al suggested that miR‐133a may be a new treatment option in diseases with hypercontractility in the pathogenesis, such as asthma, by regulating contraction via RhoA expression in smooth muscle. Kashyap et al found that miR‐132 and miR‐221 were dysregulated in rat OAB models, and these miRNAs were effective in bladder hypertrophy and dysfunction. Chermansky et al also associated dysregulation of miR‐221 and miR‐125b with patients with OAB .…”
Section: Discussionmentioning
confidence: 99%
“…In investigations of effective miRNAs in smooth muscle, Chiba et al suggested that miR‐133a may be a new treatment option in diseases with hypercontractility in the pathogenesis, such as asthma, by regulating contraction via RhoA expression in smooth muscle. Kashyap et al found that miR‐132 and miR‐221 were dysregulated in rat OAB models, and these miRNAs were effective in bladder hypertrophy and dysfunction. Chermansky et al also associated dysregulation of miR‐221 and miR‐125b with patients with OAB .…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, NGF signaling through ERK protein increases miR-222 and miR-221 levels [4]; secondly, NGF overexpresses miR-221 levels, with consequences in neuronal differentiation [5]; thirdly, NGF raises miR-21 levels, supporting its signaling and protecting cells from neuronal degeneration [136]. While all of these studies have been done on a PC12 cell line, there are also a couple of reports done in bladder [137] and bronchial epithelium [138]. …”
Section: Ngf and Mirs In Ovarian Cancermentioning
confidence: 99%
“…The authors concluded that miR34a modulates OAB susceptibility by regulating the purinergic signaling. Our group recently reported on the changes in the expression of miR‐132 and miR221 in a rat model of bladder overactivity induced by acetic acid . These prior animal and clinical studies sparked our interest in studying miRs as potential biomarkers for OAB treatments.…”
Section: Discussionmentioning
confidence: 99%
“…Total RNA was isolated from biopsy tissue using Trizol reagent. Then, the total RNA was converted to cDNA using TaqMan MicroRNA Reverse Transcription Kit (Applied Biosystems, Foster city, CA) according to manufacturer's protocol . The TaqMan primers (Life Technologies, Foster city, CA) chosen were hsa‐miR206, hsa‐miR210, hsa‐miR221, hsa‐miR26a, hsa‐miR26b, hsa‐miR125b, hsa‐miR132, hsa‐miR16, hsa‐miR124a, hsa‐miR134, hsa‐miR153, hsa‐miR199a, and hsa‐miR212.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation